Correlation between chorionic plate vascularization and risk of bronchopulmonary dysplasia in extremely preterm infants. (November 2020) - Shapiro, Svetlana; Trail-Burns, Elizabeth; Slader, Margaret G.; Laptook, Abbot; De Paepe, Monique E.
Abstract: Introduction/objectives: The chorionic plate vessels of the placenta are in direct continuity with the fetal vasculature, suggesting chorionic and fetal angiogenesis may be subjected to similar regulatory mechanisms. In this study, we determined the correlation between chorionic plate vascularization and complications of prematurity, focusing on bronchopulmonary dysplasia (BPD) and other conditions with important microvascular components. Methods: We performed a clinicoplacental analysis of 127 extremely preterm infants (23–28 weeks gestation). Chorionic plate vascularization was assessed by number and density of perforating chorionic vessels (PCVs). Charts were reviewed for relevant maternal and neonatal data, including respiratory, neurologic and gastrointestinal complications of prematurity. Results: The placentas displayed marked variability in number (36–523/placenta) and density of PCVs (0.46–3.74 PC V/cm 2 ). The median PCV density of infants with severe BPD was significantly higher than that of infants without BPD (1.51 PC V/cm 2 versus 1.09 PC V/cm 2, P  < 0.05). Conversely, the frequency of moderate-to-severe BPD was 33% higher in infants with PCV density ≥1.50 PC V/cm 2 than in those with PCV density <1.50 PC V/cm 2 (56% versus 40%, P  < 0.01). There was no correlation with neonatal neurologic or gastrointestinal complications. Conclusion: Chorionic plate vascularization correlates with frequency and severity of BPD, supporting a vascular basis that in part is antenatal in origin. Quantitative assessment of chorionic plate vascularization may allow early identification of preterm infants at high risk for BPD (proposed threshold: PCV density ≥1.50 PC V/cm 2 ). The lack of correlation between chorionic vascularization and neurologic/gastrointestinal complications suggests these conditions may have less important antenatal and/or vascular contributions. Highlights: Chorionic vascularization (perforating chorionic vessel density, PCVD) of extremely preterm placentas is highly variable. The PCVD of extremely premature infants with severe BPD is significantly higher than that of infants without BPD. Frequency of moderate-to-severe BPD is significantly higher for infants with PCVD ≥1.50 PCV/cm 2  than with lower PCVD. There is no correlation between PCVD and neurologic or gastrointestinal complications of prematurity. Quantitative assessment of chorionic plate vascularization aids in prediction of BPD risk in extremely preterm infants.